(3ZGjI GdGNJUGQs - (3GdCUagGfj, CMeO Hf GdMSjf Hf CMeO, J (B593 (3g`s ((3jMjis)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg QH GdYGdejf hHYO abO SCdfj HYV GdCUObGA Cf CYed eNJUQG aj Gdabg Ydi ePgH GdEeGe GdTGaYj aj ZGjI GdGNJUGQ aCLHJg Edi Pdcs
(3BNQgG (B:s
(3e hdO HGdhWF aj GdfcGM hUGQJ Ce hdO HGdhWF HGdTHgI hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1 / 116s
(3eYLe GdeDdajf (B1 / 125s
(3cTa GdXfhf (B2 / 1189s
(3WHbGJ GdTGaYjI ddSHcj (B4 / 38s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs